Answer:
3^(7/2) = 2.; 7^(1/2) = 1,; 3^(2/7) = 3.; 7^(2/3) = 4.
Explanation:
To convert the expressions to their radical form, we remember this formula:
![b^(exponent)/(index)=\sqrt[index]{b^e^x^p^o^n^e^n^t}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8a33kthhxjcgb52r8lozpb8ooe3o7mxr0e.png)
Thus, for 3^(7/2), 7 is the exponent and 2 is the index, which gives us
.
For 7^(1/2), 1 is the exponent and 2 is the index, which gives us
.
For 3^(2/7), 2 is the exponent and 7 is the index, which gives us
.
For 7^(2/3), 2 is the exponent and 3 is the index, which gives us
![\sqrt[3]{7^2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/979e23rkmlboeprfaz3tam6lawaj4693vl.png)